Teaching and learning computing skills via an intranet-based course - Friday, Adrian; Parkes, Alan; Nichols, David (Proceedings of the International Conference on Networked Learning, 2000)
This paper discusses a non-majorable first year University Computing course that provides novice users with fundamental computer skills. This paper-less course, now in its second year, uses combined lecture/practical sessions in addition to the Departmental intranet and the Web. The paper focuses on key issues relating to the experience of teachers and learners in this environment.